Height mismatch: An overlooked component of adult heart transplant outcomes. Issue 6 (19th April 2020) - Rudasill, Sarah E.; Sanaiha, Yas; Mardock, Alexandra L.; Xing, Hanning; Khoury, Habib; Kwon, Murray; Benharash, Peyman
Abstract: Heart transplantation guidelines recommend against matching donors with significant weight but not height discrepancies. This study analyzed the impact of donor‐recipient height mismatch on mortality among heart transplant recipients. We retrospectively analyzed all adult patients in the United Network for Organ Sharing (UNOS) registry undergoing heart transplantation from 1990 to September 2016. Moderate and severe height mismatch were classified as >10% and >15% difference in donor height from recipient height, respectively. The primary outcome was 1‐year mortality. Adjusted Cox hazards regression was performed, and Kaplan‐Meier estimates illustrated 10‐year survival. Of 44 877 transplants, 4822 (10.7%) were moderately height mismatched. Height‐mismatched recipients were more frequently female (41.6% vs 21.8%, P  < .001), sex mismatched (53.8% vs 24.9%, P  < .001), and weight mismatched (4.9% vs 1.9%, P  < .001). After adjustment, recipients of moderately (HR = 1.15 [1.02‐1.30]) and severely (HR = 1.38 [1.10‐1.74]) taller donor hearts were at increased risk of mortality at 1 year relative to height‐matched recipients. Furthermore, of 1042 (21.6%) severe mismatches, recipients with taller (HR = 1.39 [1.11‐1.74]) but not shorter (HR = 0.79 [0.44‐1.43]) donors faced increased 10‐year mortality. The effect was pronounced among re‐transplant candidates (HR = 1.96 [1.07‐3.59]). In conclusion, matching with moderately or severely taller donors is an independent predictor of mortality among primary and re‐transplant candidates.